Perancangan Purwarupa Sistem Pengendalian Kualitas Pengukuran Dimensi Produk Terotomasi - Ikhwan Arief; Rahmat Fajri Fajri (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
The production process is one of the several main activities in industries. The process followed by quality control to achieve expected final products. Products' conformities to design specification can be achieved through direct measurement. However, not all measurements can be done directly while the process is running. Inconformities to product's design specification could result in unfunctional or rejected products. This will render producers into losing their profits. Technology plays a major role in simplifying products' measurement processes. Advancement in technology made it possible to automate measurement processes and will also make it possible to do during the production process in achieving expected quality control as early as possible. The quality control yield measurements in products'lengths, widths and depths/ heights which will control products' dimension and generate quality control chart. The proposed prototype will allow measurements of product dimension and data acquisition directly during the process without disrupting on going processes.